UPAYA PEMULIHAN SEKTOR PARIWISATA DI TENGAH PANDEMI COVID 19 - Sutrisnawati, Ni Ketut; Budiasih, Ni Gusti Ayu Nyoman; Ardiasa, I Ketut (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2020)
The tourism sector is a very important sector for the people of Bali. Although the Bali region consists ofagricultural land, dry land and waters such as beaches, lakes and rivers, most Balinese depend their livelihoodson the tourism sector. Pandemic Covid -19 give a deep impact to all sectors including the tourismsector. Corona virus which is very dangerous to human health has infected millions of people around the world. The spread of the Corona virus through interactions with infected people is the reason of why socialdistance, as well as suggestions for activities at home policies made to prevent the domino effect and severthe spread of this virus. Slowly but surely the pandemi hit the tourism sector. The absence of foreign touristvisits and lockdown in some areas in Indonesia has caused tremendous impacts to tourism sector. Hotelswith 0% occupancy are temporary closed. Employees of hotels, travel and touristbusinesses, restaurantsand other sectors were laid off and most lost their jobs. The collapse of the tourism sector in Bali causedthe decline of the Balinese economy. Not only workers in the tourism sector, but farmers who supply theiragricultural products to hotels and restaurants, fishermen who sell their fish catches to hotels, as well asmedium (MSME) especially those who produce souvenirs are affected. This certainly should not be allowedto continue protracted because it will affect the continuation of life of the Balinese people. This study aimsto determine the impact caused by COVID-19 on the tourism sector along with the efforts that can be madeto restore tourism in an effort to restore the economy of the Balinese people so that Balinese people cancontinue their lives as before.